FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DYSPEPSIA PADA REMAJA DI WILAYAH KERJA PUSKESMAS KRUENG BARONA JAYA KABUPATEN ACEH BESAR TAHUN 2019 - Ari, Sari (Biotik, 2020)
Krueng Barona Jaya Aceh Health Center after being interviewed there are some patients who have unhealthy eating habits such as late eating, like eating spicy food, which can cause dyspepsia. The results of interviews of 10 people there are 8 people who experience dyspepsia. Researchers chose adolescents because many at this age generally have stress levels as well as lifestyle conditions for consuming irritating food and drink. The purpose of this study was to determine the factors that influence the incidence of dyspepsia in adolescents in the working area of Krueng Barona Jaya Aceh Besar District Health Center in 2019. This research is descriptive analytic with cross-sectional study approach. The population in this study were 38 adolescents visiting the Krueng Barona Jaya Health Center in the Juni 2019 period, with a total sample of 38 people. The sample collection technique is accidentall sampling. Data analysis using univariate and bivariate, research was carried out in 17 s/d 24 June 2019. The results showed that there is a relationship between stress (p-value 0.033), regularity of food (p-value 0.004), irritative food and drinks (p-value 0.024) with the occurrence of dyspepsia in adolescents in the working area of Krueng Barona Jaya Aceh Besar Regency Health Center in 2019. It is recommended for adolescents, it is necessary to make a meal schedule and always maintain the availability of food when mealtime arrives or by always bringing snacks, pay attention to regular meal times (right) and types of food adequate and varied, which consists of carbohydrates, protein, and fat at every meal, and avoid the consumption of spicy foods, sour, soft drinks.